How to use images - Marshall, Lindsey; Maechem, Lester (London Laurence King Publishing Ltd., 2010)
Fundamental to the study of graphic design is the creative use of images in a design context. This book teaches you how to select and use images for a range of applications, including: magazines and newspapers, posters, booklets, books, leaflets, stationery, book and CD covers, advertising and promotional material, packaging, point of purchase, web pages and digital advertisements. It explores methodologies for choosing, placing, combining, manipulating and montaging imagery and the relationship of image to text, with chapters on: Selection, Structure and layout, Composition, Communication, Color, Image potential, and Production. Using fully illustrated case studies from leading graphic designers and practical exercises, the book provides professional insights and tips into ways of using pictures to maximum effect.
Keywords: Visual communication; Visual perception; Communication and technology; Graphic arts; Design; Nonverbal communication